Financial Independence of Central Bank through the Balance Sheet Prism - Valentina Ivanović (Journal of Central Banking Theory and Practice, 2014)
The main reason for central bank independence lies in the fact that it is necessary to clearly distinguish spending money from the ability of making money. Independence of central banks is now a characteristic of almost all developed and highly industrialized countries. In this respect, it represents an essential part of the overall economic reality of these countries. Over the past decade or somewhat earlier, the issue of importance of central bank independence has been raised in developing countries, making the institutional, functional, personal and financial independence of central banks current topics for consideration. The key reason for the growing attention to financial independence of central banks is due to the effects of the global financial crisis on their balance sheets and therefore the challenges related to achieving the basic goals of the functioning of central banks - financial stability and price stability. Financial strength and independence of central banks must be developed relative to the policy and tasks that are carried out and risks they face in carrying out of these tasks. Financial independence represents a key base for credibility of a central bank. On one hand, the degree of credibility is associated with the ability of central banks to carry out their tasks without external financial assistance. In order to enhance the credibility of central bank in this regard, it must have sufficient financial strength to absorb potential losses and that power must be continuously strengthened by increasing capital and rearranging profit allocation arrangements. This is particularly important in times of crisis.
Keywords: E52; E58; 330; central bank; financial independence; independence indices; financial crisis; balance sheet; capital; profit allocation; budget management